2021
DOI: 10.3889/oamjms.2021.5982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Activity of Botto-Botto Leaf Fraction (Chromolaena Odorata L.) Using DPPH and ABTS Methods

Abstract: BACKGROUND: Antioxidants are substances that can inhibit the oxidation process, so that they have a protective effect on cells from the dangers of free radicals. One of the plants that has activity as natural antioxidants is Botto-Botto leaves (Chromolaena odorata L.). AIM: This study aims to determine the antioxidant activity of the Botto-Botto leaf fraction using the DPPH and ABTS methods. METHODS: The leaves of Botto-Botto (Chromolaena odorata L.) obtained from Takalar District, South Sulawesi are sorted, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Very low IC 50 value of essential oil supports the significance of E. odoratum leaves as a promising herbal source of antioxidant compounds, hence can be utilized in nutritional as well as pharmaceutical in industries.Raman et al, 23 reported the DPPH scavenging activity of aqueous and methanol extracts of E. odoratum having IC 50 values 10.5µg/ml and 10.2µg/ml, respectively, that are comparable to the present study. Tahir et al, 24 performed antioxidant activity of the leaf extract by DPPH method, and reported n-butanol fraction have maximum activity with IC 50 value at 33.535µg/ ml. Another study revealed that the DPPH assay of ethyl acetate fraction had the highest antioxidant activity, with IC 50 value of 10.05±0.06 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Very low IC 50 value of essential oil supports the significance of E. odoratum leaves as a promising herbal source of antioxidant compounds, hence can be utilized in nutritional as well as pharmaceutical in industries.Raman et al, 23 reported the DPPH scavenging activity of aqueous and methanol extracts of E. odoratum having IC 50 values 10.5µg/ml and 10.2µg/ml, respectively, that are comparable to the present study. Tahir et al, 24 performed antioxidant activity of the leaf extract by DPPH method, and reported n-butanol fraction have maximum activity with IC 50 value at 33.535µg/ ml. Another study revealed that the DPPH assay of ethyl acetate fraction had the highest antioxidant activity, with IC 50 value of 10.05±0.06 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…This plant is spread all over the world in almost all types of habitats (Aziz, et al, 2020). This plant contains acacetin, chalcones, eupatilin, luteolin, scutellareintetramethyl ether, and sinensetin that have been known to exhibit antibacterial activity, anti-fungi, and antioxidant properties (Atindehou, et al, 2013;Sirinthipaporn & Jiraungkoorskul, 2017;Zahara, 2019;Tahir, et al, 2021). C. odorata is easy to find and has potential source of compounds to be used as a co-chemotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%